Exploring Grammarly's Effectiveness in EFL Writing through a Student Perception Study - Amalia Maypida; Emeliya Sukma Dara Damanik (The Journal of Educational Development, 2024)
The study explored the effectiveness of Grammarly as a supportive tool in enhancing English as a Foreign Language (EFL) writing skills, based on students' perceptions. The research aimed to identify the advantages and disadvantages experienced by students using Grammarly in their writing activities. Data were collected from 30 higher education students at UIN Sumatera Utara Medan, who participated in EFL writing classes. The methodology involved questionnaires and interviews, with the questionnaires comprising 12 statements on Grammarly's usage intensity and effectiveness. Five students were selected for in-depth interviews to gain further insights into their experiences. The results indicated that students generally had positive perceptions of Grammarly, appreciating its ability to minimize grammatical errors, improve language style, and enhance word choice and punctuation. However, some drawbacks were noted, such as the need for a stable internet connection and the limited functionality of the free version. The conclusion of the study affirmed that Grammarly is a valuable tool for supporting EFL writing, providing clear and detailed feedback that helps students produce more accurate and polished written work. This research contributes to the understanding of technology-assisted language learning tools and their impact on student writing proficiency.